The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1590/s0104-530x2013000100012
|View full text |Cite
|
Sign up to set email alerts
|

Modelo de referência para o processo de desenvolvimento de produtos mecatrônicos (MRM): validação e resultados de uso

Abstract: Este artigo apresenta o modelo de referência para o desenvolvimento de produtos mecatrônicos (MRM) enfatizando o trabalho de validação do modelo pela implantação de melhorias no processo de desenvolvimento de produtos (PDP) de uma empresa desenvolvedora. A aplicação e validação do modelo foi realizada por meio de uma pesquisa-ação. O conteúdo do modelo é sumarizado e sua metodologia de aplicação e validação é apresentada. As melhorias introduzidas aumentaram a capabilidade do PDP da empresa tanto na análise do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…CMMI suggests that it has two possible directions for process improvements based on the third party approaches: a whole company improvement based on maturity levels and a sector-specific improvement approach based on capability assessment (Chrissis et al, 2003). Some literature discusses capability-based improvements Schuh et al (2017), Barbalho and Rozenfeld (2013), Barbalho and Rozenfeld (2008), but generally, the concept of maturity assessment and improvement is more commonly applied (Schuh et al, 2017;Agca et al, 2017;Carolis et al, 2017). In other words, capability-based improvements tend to generate performance islands, as suggested by Vernadat (1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…CMMI suggests that it has two possible directions for process improvements based on the third party approaches: a whole company improvement based on maturity levels and a sector-specific improvement approach based on capability assessment (Chrissis et al, 2003). Some literature discusses capability-based improvements Schuh et al (2017), Barbalho and Rozenfeld (2013), Barbalho and Rozenfeld (2008), but generally, the concept of maturity assessment and improvement is more commonly applied (Schuh et al, 2017;Agca et al, 2017;Carolis et al, 2017). In other words, capability-based improvements tend to generate performance islands, as suggested by Vernadat (1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Os modelos de referência podem ser entendidos como diretrizes, procedimentos e critérios de decisão para que ocorra o sucesso no PDP (BARBALHO & ROZENFELD, 2013 Quando há possibilidade de geração de um produto novo, necessita-se ter atenção no processo de projeto que será utilizado, isso para que o produto incorpore todos os atributos que são indispensáveis para o cumprimento da tarefa a que se destina (REIS & FORCELLINI, 2006). Nesse sentido, conforme SCALICE et al (2012), vários autores relatam a importância de um correto e completo projeto das interfaces de um produto.…”
Section: Introductionunclassified
“…The study of BARBALHO & ROZENFELD (2013) demonstrated that the application of a reference PDP model might result in process improvement, reporting better indicators of time, cost and quality of the PDP.…”
Section: Introductionmentioning
confidence: 99%